The Effectiveness of Red Ginger Decoction Water to Accelerate The Healing of Perineal Laceration Wounds in Physiological Puerperal Mothers - Idayanti, Titiek; Anggaraeni, Widya (Jurnal MIDPRO, 2022)
A perineal wound is a wound on the area between the vulva and the anus that occurs during the labor process.Â  Wounds can heal if properly treated. Treatment of perineal wounds can be helped by non-pharmacological means.1 Herbal ingredients that can be used in accelerating the healing of perineal wounds are red ginger boiled water (Zingiber officinaleVar.Rosc.Rubrum). The content of red ginger compounds has an active substance that functions as an anti-inflammatory, namely gingerol. 2The design of this study used quasi-experimentation with a posttest only control group design with a total sample of 20 respondents, taken by consecutive sampling. Results: respondents who were given treatment by giving red ginger boiled water were said to be cured, namely. as many as 10 patients (100%), while respondents who were not given treatment by giving red ginger boiled water were said to be not cured, namely as many as 8 patients (80%). From the results of the study using the Mann Whitney U statistical test, the Z value was -3,559. The Sig value or P Value is 0.000 < 0.05.Â  If the p value of the < the critical limit is 0.05. Discuss: Drinking red ginger decoction water is effective in accelerating the healing of perineal wounds in puerperal mothers.